PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATA PELAJARAN INFORMATIKA DI SMK NEGERI 4 PADANG - Satria Veri; Heri Mulyono; Ade Pratama (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The point of this examination is to convey Android-based learning materials in the computational reasoning material informatics subject at SMK Negeri 4 Padang on computational reasoning material. This exploration utilizes an innovative work approach. The advancement model utilized in this exploration is the ADDIE model. The examination subjects utilized were understudies of State Professional School class The exploration instrument is an important device since it utilizes a substantial survey with 6 validators. The verification interaction incorporates 3 media validators and 3 equipment validators. The viable device involves a survey for 18 understudies and 3 teachers. The item made in this examination is an Android-based learning apparatus. In view of the media approval results, an Android-based media approval score of 83.75 was acquired in the